2005
DOI: 10.1111/j.1440-1711.2005.01308.x
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus saimiri immortalization of Aotus T lymphocytes specific for an immunogenically modified peptide of Plasmodium falciparum merozoite surface antigen 2

Abstract: SummaryThe Plasmodium merozoite surface antigen 2 (MSA2) is one of several candidates for a protective vaccine against malaria. Previous studies have shown that antibodies directed against the MSA2 variable region are not protective and that constant regions are non-immunogenic. However, modified peptides derived from constant regions can be rendered immunogenic and partially protective in Aotus monkeys. In this study, we reveal the establishment, using in vitro Herpesvirus samiri (HVS) infection, of an Aotus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…There is some discussion about using D ‐peptides for chaperone systems39 and for inducing protective immunity 40. Shai and colleagues reported that a synthetic D ‐amino acid peptide that corresponded to the N‐ terminal sequence of HIV‐1 gp41 ( D ‐WT) of HIV‐1 associates with its enantiomeric wild‐type fusion (WT) peptide in the membrane and inhibits cell fusion mediated by the HIV‐1 envelope glycoprotein 41.…”
Section: Resultsmentioning
confidence: 99%
“…There is some discussion about using D ‐peptides for chaperone systems39 and for inducing protective immunity 40. Shai and colleagues reported that a synthetic D ‐amino acid peptide that corresponded to the N‐ terminal sequence of HIV‐1 gp41 ( D ‐WT) of HIV‐1 associates with its enantiomeric wild‐type fusion (WT) peptide in the membrane and inhibits cell fusion mediated by the HIV‐1 envelope glycoprotein 41.…”
Section: Resultsmentioning
confidence: 99%
“…Differences in degree of susceptibility or immunity to experimental malarial infection and differences in serum proteins correspond to the red-or gray-necked group type. While the owl monkey is an excellent animal model for human malaria and its treatment, it has also been identified as a model for studies of oncogenic viruses, particularly herpesviruses (Barhona et al, 1976;Vernot et al, 2005), and nononcogenic viruses such as hepatitis A (Asher et al, 1995;Balayan, 1992), and it has shown potential as a model for Eastern equine encephalitis virus (Espinosa et al, 2009) and dengue virus (Schiavetta et al, 2003). Both of these Aotus spp.…”
Section: Research Usesmentioning
confidence: 99%
“…HVS infection transforms both non-human primates and human T-cells to TCR-independent proliferation [ 18 20 ]. Tip binding to Lck and subsequent Lck activation are partially responsible for this effect [ 24 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…HVS infection has been used in vitro in human and non-human primates ( Aotus spp.) as a strategy for T-cell transformation [ 18 20 ]. This would suggest that transformation mechanisms in human and Aotus T-cells could have the same molecular basis.…”
Section: Introductionmentioning
confidence: 99%